(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
During the direct work in teaching interior design of residential and public objects with students in the specialty "Engineering Design" at the University of Forestry, in Sofia, Bulgaria it was found that they have particular difficulties in applying the design methodology in practical briefs and work. For this reason, the present work was made. The report clarifies the stages of project assignment implementing, which accompanied by the basic concepts in the design assignment theory and practice in Bulgaria gives the key to the successful creation of a harmonious interior composition, both in public and in residential buildings.